PRICE REVIEW ANALYSIS ON CRYPTOCURRENCIES IN INDONESIA - Olga, Olga; Muhammad Fauzan; Bayu Fajar Susanto (Indragiri Research Center (ingreat), 2023)
The purpose of this study is to analyze the price review of Cryptocurrencies in Indonesia. This research uses qualitative research methods with the nature of literature review. qualitative research conducted and research purposes, sampling may not be necessary in qualitative research with a literature review. In this case, the researcher did not collect data from respondents or informants, so there was no need to take samples. The results of the study show that cryptocurrency prices in Indonesia are still considered digital assets and have not been recognized as legal currency. Nonetheless, Cryptocurrency transactions still occur in Indonesia and several Cryptocurrency exchanges also operate in Indonesia by complying with regulations set by the government. The development of blockchain technology and Cryptocurrency adoption continues to increase in Indonesia, and the Indonesian government has also introduced initiatives such as the Blockchain Indonesia program to increase awareness and adoption of blockchain technology in Indonesia. As an investor, keep in mind that Cryptocurrency is still very risky and very volatile. Therefore, it is necessary to be careful and carefully consider the risks before deciding to invest. It is also important to always follow the regulations and policies related to Cryptocurrency set by the Indonesian government.